Child-Friendly School Environment Management - Mohammad Sofwan Effendi; Supadi (Jurnal Pendidikan Indonesia, 2023)
Implementing child-friendly schools must be based on principles without violence or discrimination against disability, gender, ethnicity, religion, or parental background. Obstacles in creating Child-Friendly school include the need for more complete and adequate facilities. Educators also do not have the ability to implement Child-Friendly school. Therefore this study aims to analyze how environmental management realizes Child-Friendly Schools. This study used qualitative descriptive methods. The data collection techniques use in this study is through observation, interviews, and documentation. Data is analyzed interactively by data reduction, data presentation, and conclusions. The results showed that environmental management followed the components of child-friendly schools well. That can be seen from the average value of statement items on the child-friendly school indicator which shows respondents' answers tend to agree and strongly agree. However, several suggestions need to be considered: transparency in preventing students from dropping out of school, increasing health requirements, and cooperation with various related parties.